The Material Co-text of the Kantu` Dayak Gawai Tradition West Kalimantan - Sigit Widiyarto; Dadang Sunendar; Sumiyadi Sumiyadi; Tedi Permadi (Budapest International Research and Critics University, 2022)
This study aimed to describe the material co-text of the Gawai Dayak tradition of the Kantu tribe of West Kalimantan. In addition, research was also to find out what materials are used in the Gawai Dayak tradition. This research was descriptive qualitative. Data were taken by means of direct interviews, observation and documentation. For the validity of the data, the study used data triangulation techniques. The research respondents were 5 people, consisting of the community, tradition observers and the village head of Ranyai, West Kalimantan. The results showed that the material context of the Gawai Dayak tradition consists of equipment and food. The food offerings consisted of Pulut, Jawak, Seed of paddy, Cocunut, The seed of cucumber, Sugar, Eggs, Betel nut, Chicken(manok) Tuak (fermantion drink). While the equipment includes nampah, plates, small baskets, and bamboo squares and other tools. All tools and food offerings have meaning and purpose that could be closer to the true meaning of life.